Digital Transformation in Personnel Management: Organizational Communication Strategy of e-HRM at the Sumatra III River Basin Agency - Ernila Sari Rahman; Anuar Rasyid; Muhammad Firdaus (Journal of Communication Studies, 2025)
Digital transformation in the public sector requires government organizations to optimize information technology, including personnel management through Electronic Human Resources Management (e-HRM). The Sumatra III River Basin Agency has implemented e-HRM since 2017; however, its utilization has not been fully optimized due to low employee participation in updating personnel data. This study aims to analyze organizational communication strategies in the implementation of e HRM from the aspects of planning, implementation, and evaluation. This research employed a descriptive qualitative approach through in-depth interviews, observation, and documentation. The findings reveal that communication planning was carried out through top-down policies, socialization, and training, but remained largely instructional in nature. Communication implementation involved vertical, horizontal, and diagonal flows, with vertical communication as the dominant pattern. Communication evaluation has been conducted; however, it remains administrative and has not been sustainable in fostering changes in organizational work culture. This study confirms that the success of e-HRM implementation depends not only on technological readiness but also on participatory, collaborative, and sustainable organizational communication strategies to support bureaucratic digital transformation.